Os efeitos das queima de biomassa sobre a saúde humana no município de Marabá - PA - DIAS, Yuri Alefh Saraiva (2023)
The objective of this study was to investigate the association of heat and biomass fires with hospital admissions in the population from 0 to 89 years of age from respiratory diseases (DRs) in the period from 2007 to 2017. The weather data was acquired on the INMET website in the database that provides this historical data. The hot spots were acquired on the INPE website and the hospital admission data were obtained by the SUS - DATASUS database. Statistical methods were used, such as Pearson's correlation to correlate the data of the meteorological factors with the data of hospital admissions, the significant values were considered + 0.5 values of positive correlation or - 0.5 of negative correlation. It was observed that the Marabá region presents low humidity and precipitation in the months of August, September and October, higher temperature and hot spots. The highest hospitalization rates were observed during the rainy season, between March and June. Significant positive association of climatic variables and heat sources with hospital admissions by (DRs) was observed. In 2007 in three cases temperature and heat sources, In the year 2008, with temperature and hot spots, In the year 2009, temperature and humidity, In the year 2010, temperature and heat outbreaks, In the year 2011, temperature and heat sources, In the year 2012, precipitation and humidity, In the year 2013, precipitation, humidity, temperature and with foci of heat, In the year 2014, temperature and heat outbreaks, In the year 2015, and humidity, In the year 2016, temperature and hot spots, In the year 2017, precipitation, temperature and humidity. In addition to using the Moran I index, for the creation of cluster map and dispersion chart, with the purpose of making a spatial correlation of the heat sources with the resident population in 2010.